Microfluidic system for high throughput characterisation of echogenic particles. Issue 2 (4th November 2014) - Rademeyer, Paul; Carugo, Dario; Lee, Jeong Yu; Stride, Eleanor
Abstract : We present the design and performance of a microfluidic based system, capable of accurately measuring the response of echogenic micro/nano particles to ultrasound excitation. Abstract : Echogenic particles, such as microbubbles and volatile liquid micro/nano droplets, have shown considerable potential in a variety of clinical diagnostic and therapeutic applications. The accurate prediction of their response to ultrasound excitation is however extremely challenging, and this has hindered the optimisation of techniques such as quantitative ultrasound imaging and targeted drug delivery. Existing characterisation techniques, such as ultra-high speed microscopy provide important insights, but suffer from a number of limitations; most significantly difficulty in obtaining large data sets suitable for statistical analysis and the need to physically constrain the particles, thereby altering their dynamics. Here a microfluidic system is presented that overcomes these challenges to enable the measurement of single echogenic particle response to ultrasound excitation. A co-axial flow focusing device is used to direct a continuous stream of unconstrained particles through the combined focal region of an ultrasound transducer and a laser. Both the optical and acoustic scatter from individual particles are then simultaneously recorded. Calibration of the device and example results for different types of echogenic particle are presented, demonstrating a high throughput of up to 20 particles per second and the ability to resolve changes in particle radius down to 0.1 μm with an uncertainty of less than 3%.